COMMUNITY EMPOWERMENT OF PALOH IGEUH VILLAGE IN EFFORTS TO IMPROVE ECONOMIC AND BUSINESS INDEPENDENCE THROUGH OYSTER MUSHROOM CULTIVATION AND ITS PROCESSED - Sri Wahyuni; Muthaharah Muthaharah; Azhari Azhari (Global Science Society, 2021)
Oyster mushroom cultivation business is one way to increase income and people’s nutritional, especially during Covid-19 pandemic. The purpose of this activity is carried out through preparation methods, socialization, training, business planning and product marketing, also program evaluation with village community. The target groups are the Family Walfare Empowerment (PKK), youth organization, farmers, traders, and stakeholders. The results obtained are the formation join business group, formation creative and innovative communities to processed product of oyster mushroom, and the creation people who are aware and care about better income and welfare.